Pengaruh Substitusi Tepung Tapioka Dengan Tepung Kulit Pisang Kepok Terhadap Kandungan Gizi, Serat Pangan dan Daya Terima Bakso Daging - Anissa Pratiwi Darmawan (2021)
The risk of obesity can be increased by an increase in sugar and fat consumption and a lack of fiber consumption. Banana peel is one of the by-products of food that can be used because it contains high fiber. The purpose of this study was to analyze the effect of substitution of tapioca flour with kepok banana peel flour on nutritional content, dietary fiber and acceptability of meatballs. This research is an experimental research design with one factor Completely Randomized Design (CRD) with two repetitions. The factor is the meatball formula which is divided into 4 formulas with each percentage level of addition of kepok banana peel flour, namely F0 0%, F1 10%, F2 15%, and F3 20%. Analysis of nutritional content, dietary fiber and organoleptic was tested using ANOVA and Kruskall Wallis tests, respectively. If there is a significant difference, further tests are carried out. The results of the analysis showed that the level of addition of kepok banana peel flour had a significant effect (p<0.05) on the fiber content and significantly (p=0.00) on the panelists' preference level on the parameters of color, aroma, texture and taste of meatballs with banana peel flour. knock. The chosen formula is meatball F3 with the addition of 20% kepok banana peel flour which has a water content of 67.63%, ash content of 1.53%, protein content of 11.04%, fat content of 5.55%, carbohydrate content of 14.29 % and food fiber content of 44.71%.